SOSIALISASI PEMANFAATAN LIMBAH PLASTIK SEBAGAI BAHAN PEMBUATAN PAVING BLOK DI DESA SUMBER REJO KABUPATEN MUSI RAWAS - Yeni Trianah; Santi Sani (JURNAL CEMERLANG : Pengabdian pada Masyarakat, 2023)
The problem of plastic waste in Indonesia is one of the most difficult problems to solve, because most of the plastic waste cannot be recycled, this causes a waste crisis in Indonesia and makes Indonesia the fourth country with the most use of plastic waste in the world. This community service activity aims to socialize in processing plastic waste into paving blocks which are given to the partners of Sumber Rejo village residents. In carrying out this socialization, it is hoped that it will be a process of utilizing appropriate science and technology in utilizing plastic waste in the surrounding environment so that it can be used by the community in making paving blocks and having high selling value. The result of this activity is the socialization of making paving blocks by utilizing plastic waste. Based on the results of the community service that has been carried out, it can be concluded that the level of public understanding of the manufacture of paving blocks is increasing.